Patent Ductus Arteriosus (P.D.A.) (An analysis of 37 surgically proved cases) - O. J. Rachman; A. Hanafiah; I. S. F. Ranti (Paediatrica Indonesiana, 2019)
An analysis of the clinical picture on 37 cases of patent ductus arteriosus proved by operation is presented, including the chest X-ray and electrocardiographic findings.